A STUDY OF WOMEN, S EDUCATION IN RURAL AREAS OF JAMMU AND KASHMIR WITH SPECIAL REFERENCE TO RAMBAN DISTRICT. - Priksha Raina (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Education is considered as one of the most powerful instruments of social change and control. Education can remove darkness of ignorance and narrow-mindedness of human mind and infuse new ideas, new light and new direction for change and development. Due to conservative traditionalism, the standing of women has always been viewed next to than that of men in our nation. Because of the reliance of women on males for financial support (families did not think it is important to provide education to girls), they were mostly seen as subservient to men. In Indian society, well known for its cultural diversity, we can see sharp multiple inequalities and disparities in education and economic development in terms of caste, creed, tribe, religion and gender despite prolonged struggle and affirmative action by the state to reduce social inequalities in independent India. But in spite of constitutional provisions, policies, and programmes in favour of women, increase of literacy rate and promotion of girl’s education, many social evils practices and customs still exist in our society which prevents girl from availing opportunities available for them. girls in general, constitute the most deprived and disadvantaged section of Indian society who have always faced multiple barriers in getting educational opportunities. In independent India, however, girls have made significant strides by entering in every field of education. Even then, a large number of women especially who reside in rural area remain restricted to vicious circles of family expectations, gender discrimination and stigma. Available literature reveals an increase in women literacy rate in the last few decades but still there is a wide gap between boys’ and girls’ literacy rate. The rural girl’s literacy rate in J&K as per 2011 census report is 53.36 percent and for urban females is 70.19 percent when compared to earlier in the Census of 2001 was 36.7% at rural and 61.9% at the urban level, respectively. Within Jammu and Kashmir rural- urban differentials in terms of literacy rate are quite wide. Literacy rate is quite high in districts with higher urban population which are concentrated mostly in plain areas as compared to those districts which are primarily mountainous and have low level of urbanisation. The present study attempt to analysed the educational status of girls in rural areas of ramban district.